2008
DOI: 10.1371/journal.pbio.0060135
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the DLK1-DIO3 Imprinted Domain in Mammals

Abstract: A comprehensive, domain-wide comparative analysis of genomic imprinting between mammals that imprint and those that do not can provide valuable information about how and why imprinting evolved. The imprinting status, DNA methylation, and genomic landscape of the Dlk1-Dio3 cluster were determined in eutherian, metatherian, and prototherian mammals including tammar wallaby and platypus. Imprinting across the whole domain evolved after the divergence of eutherian from marsupial mammals and in eutherians is under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 53 publications
7
153
0
3
Order By: Relevance
“…Evolutionary studies of imprinted regions indicate that imprinted ncRNAs are more responsible for the origin and evolution of genomic imprinting than imprinted proteincoding genes (see Introduction); however, current evolutionary analyses of both imprinted ncRNAs and imprinted regions are limited to several well known examples (Paulsen et al 2005;Edwards et al 2008;Glazov et al 2008;Nahkuri et al 2008;Smits et al 2008;Zhang and Qu 2009). To undertake broader studies of more imprinted regions, a full list of known imprinted regions becomes necessary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolutionary studies of imprinted regions indicate that imprinted ncRNAs are more responsible for the origin and evolution of genomic imprinting than imprinted proteincoding genes (see Introduction); however, current evolutionary analyses of both imprinted ncRNAs and imprinted regions are limited to several well known examples (Paulsen et al 2005;Edwards et al 2008;Glazov et al 2008;Nahkuri et al 2008;Smits et al 2008;Zhang and Qu 2009). To undertake broader studies of more imprinted regions, a full list of known imprinted regions becomes necessary.…”
Section: Resultsmentioning
confidence: 99%
“…It is imprinted ncRNAs, rather than protein-coding genes, that coexist with large imprinted regions and may contribute to the evolution and regulation of genomic imprinting. Evolutionary studies have indicated that most imprinted protein-coding genes are well conserved between species that use imprinting and species that do not use imprinting; however, examined imprinted ncRNAs are present only in organisms that use imprinting (Hore et al 2007;Edwards et al 2008;Nahkuri et al 2008;Smits et al 2008;Zhang and Qu 2009). A great deal of small imprinted ncRNAs, which cluster in imprinted regions and vary among mammals, were predicted to be associated with the acquisition and expansion of genomic imprinting (Glazov et al 2008;Zhang and Qu 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It will be interesting to determine why selective pressures have acted to control gene dosage by imprinting at some loci and not at others in metatherian mammals. No evidence exists for imprinting in oviparous mammals such as the platypus or the echidna (Suzuki et al 2007;Edwards et al 2008). …”
Section: Imprinting In Various Mammalian Speciesmentioning
confidence: 99%
“…All genes in this domain together with the 47 miRNAs are developmentally regulated and expressed in a range of embryonic and extra embryonic tissues with postnatal expression being found predominantly in the adult brain (Seitz et al 2004, Tierling et al 2006. Although the protein-coding genes within the Dlk1-Dio3 region are highly conserved during evolution, the miRNA cluster is conserved only in mammals (Edwards et al 2008). The functions of these genes and miRNAs are largely unknown.…”
Section: Type 3 Iodothyronine Deiodinasementioning
confidence: 99%